Success rate, efficacy, and safety/tolerability of overnight switching from immediate‐ to extended‐release pramipexole in advanced Parkinson's disease. Issue 1 (31st July 2012) - Schapira, A. H. V.; Barone, P.; Hauser, R. A.; Mizuno, Y.; Rascol, O.; Busse, M.; Debieuvre, C.; Fraessdorf, M.; Poewe, W.
<x xml:space="preserve">Abstract</x> Background and purpose For Parkinson's disease (PD), an extended‐release (ER) pramipexole formulation taken once daily, has shown efficacy, safety, and tolerability resembling those of immediate‐release (IR) pramipexole taken three times daily. The present study assessed, in advanced PD, the success of an overnight switch from adjunctive IR to ER. Methods Levodopa users experiencing motor fluctuations were randomized to adjunctive double‐blind (DB) placebo, IR, or ER. Amongst completers of ≥18 weeks, ER recipients were kept on DB ER, whilst IR recipients were switched overnight to DB ER at unchanged daily dosage. After a DB week, switch success was assessed. During the next 5 weeks, all patients underwent ER titration to optimal open‐label maintenance dosage. Results One week post‐switch, 86.2% of 123 IR‐to‐ER and 83.8% of 105 ER‐to‐ER patients had ≤15% (or ≤3‐point, for pre‐switch scores ≤20) increase on UPDRS Parts II + III, and 77.9% (of 122) and 70.2% (of 104) had ≤1‐h increase in daily OFF‐time. At 32 weeks, the groups showed comparable improvements from DB baseline (pramipexole inception), including, on UPDRS II + III, adjusted mean (SE) changes of −14.8 (1.5) for IR‐to‐ER and −13.3 (1.6) for ER‐to‐ER. Rates of premature discontinuation owing to adverse events were 6.5% for IR‐to‐ER and 4.9% for ER‐to‐ER. Conclusions By OFF‐time and UPDRS criteria, majorities of patients with advanced PD were successfully switched overnight from pramipexole IR to ER at unchanged daily dosage. During subsequent maintenance, pramipexole showed sustained efficacy, safety, and tolerability, regardless of formulation (IR or ER) in the preceding DB trial.